Morphometric evaluation of the body and odontoid process of the axis vertebra and its clinical significance. A cross-sectional anatomical study. - Veerraju, Adabala N. V. V. (Student's Journal of Health Research Africa, 2025)
Introduction: The axis, which is the second cervical vertebra, serves as a pivot, allowing the atlas to rotate and support the head. Despite its small size, this area can lead to significant complications because of the intricate anatomy of the cranio-cervical junction. The axis vertebra is distinct because it features a dens or odontoid process. Fractures of the dens in the axis account for 7–27% of all cervical spine fractures. Surgical procedures in the craniovertebral region carry a high risk, as vertebral artery injury is common. Therefore, a comprehensive understanding of the anatomy of the body and the odontoid process of the axis vertebra is essential. Materials and methods: A cross-sectional study was carried out using fifty-two intact dry human axis vertebrae of unspecified sex. Measurements of the body and odontoid process of these vertebrae were obtained with a digital vernier caliper, which has an accuracy of up to 0.01mm. Statistical analysis was performed using IBM SPSS Version 21. Results: The body of the axis vertebra measured as follows: mean length of the body, 14.93±1.11 mm; vertebral body superior width, 15.79±1.76 mm; vertebral body inferior width, 16.22±1.31 mm; vertebral body anterior height, 18.69±2.17 mm; and vertebral body posterior height, 15.96±1.89 mm. The odontoid process of the axis vertebra measured as follows: odontoid process height, 17.60±1.94 mm; odontoid process anteroposterior diameter, 10.61±0.85 mm; maximum transverse diameter of the odontoid process, 9.78±0.93 mm; minimum transverse diameter of the odontoid process, 8.53±0.82 mm; atlanto-odontoid facet height, 9.67±1.43 mm; and atlanto-odontoid facet width, 7.86±0.90. Conclusion: These measurements are essential for the safe and effective application of modern orthopedic techniques. This data helps surgeons in reducing complications such as vertebral artery injury and other vital structures during surgical procedures in the cranio-vertebral region. Recommendations: Future studies should include larger, diverse samples with radiologic correlation.